MASYARAKAT MADANI; PLURALITAS DALAM ISYARAT AL-QURÃ¢â¬â¢AN - Elkarimah, Mia Fitirah (EDUKASI: Jurnal Pendidikan Islam, 2016)
People who are aware of the rights of citizens and carrying out his duty as a citizen, civilized, uphold humanitarian values, as well as the mastery of science and technology advance in the so-called civil society. This model of society as a dream of idealism and a focus for the world community to this day. Actually this discourse comes alongside the emerging issues of democratization and human rights, which means the same. Madani society is the greatest contribution in building a democracy in a country. And democracy will be realized if the people are aware of respect for human rights. The authors limited the concept of Madani society in the Quran cues associated with the concept of baldatun toyyibatun warobbun gofur and the concept of ummah, thus giving rise to one of the characteristics of this community is harmony in plurality.Masyarakat madani sebuah istilah yang merupakan masyarakat yang sadar akan hak-hak warga masyarakat dan melaksanakan kewajibannya sebagai warga negara, beradab, menjunjung tinggi nilai-nilai kemanusiaan, serta maju dalam penguasaan iptek. Masyarakat madani menjadi impian dan fokus idealisme bagi masyarakat dunia sampai saat ini. Sebenarnya wacana ini hadir bersamaan dengan maraknya issu demokratisasi dan HAM, yang masing-masing mempunyai hubungan yang tidak dapat dipisahkan. Masyarakat madani merupakan sumbangan terbesar dalam membangun sebuah demokrasi dalam suatu negara. Dan demokrasi tersebut akan bisa terwujud kalau manusia sadar untuk menghargai hak asasi manusia. Adapun penulis membatasi konsep masyarakat madani dalam isyarat Al-QurÃ¢â¬Å¸an dengan dikaitkan konsep baldatun thayyibatun wa rabbun ghafÃÂ«r dan konsep Ummah, sehingga memunculkan salah satu ciri dari masyarakat ini adalah kerukunan dalam pluralitas.